ANALISIS YURIDIS PENERAPAN PERATURAN MENTERI PERHUBUNGAN NOMOR 92 TAHUN 2011 TENTANG TANGGUNG JAWAB PENGANGKUT ANGKUTAN UDARA ATAS KETERLAMBATAN DAN PEMBATALAN JADWAL KEBERANGKATAN PENUMPANG ANGKUTAN UDARA (STUDI PADA PT. SRIWIJAYA AIR MEDAN) - ANDRIAN HIDAYAT (University of North Sumatera, 2013)
Abstract: Air transport is the kind of efficient transportation to take a journey, so that the great demand of society as professionals or business. But the problem that needs to be noted is the event delay and cancellation of scheduled air transport passenger departures that result in losses for both parties i.e. the carrier and the passenger. Regulation of the Minister of transportation Number PM 77 in 2011 as modified with the number PM 92 in 2011 About the responsibility of air freight Transport have been issued as a follow-up on the matter. Of research results drawn conclusion that PT. Sriwijaya Air flight as the company was able to implement the regulation as a form of liability towards passengers. Kata Kunci : Tanggung Jawab Pangangkut, Keterlambatan, Pembatalan Keberangkatan.